Biocidal Effect of Essential Oil of Verbena Officinalis on the Black Bean Aphis Fabae - M, MehaniL (Open Access Journal of Mycology & Mycological Sciences, 2023)
The polyphagia and the great capacity of reproduction of the aphids, arouse the use of several control methods, among others, essential oils which constitute a good alternative to the fight chemical and one of the most explored pathways in the biological regulation of pests. The aim of the study is to estimate the insecticidal power of a bio product formulated from an oil bitter Verbena officinalis, on the reduction of fertility and population density of different biological forms of the black bean aphid Aphis fabae. The temporal effectiveness of the formulated bio product was estimated by evaluating the rates of residual populations Methods: The essential oil is extracted by hydrodistilation from Verbena officinalis leaves. After formulation, two doses were recommended (D=0.4g/l and DD=1g/l), and two treatment methods were used (foliar application and root absorption) on broad bean plants infested by Aphis fabae with the aim of highlight the insecticidal capacity of the essential oil of Verbena officinalis. The results showed that the two treatment modes have a very marked effect on the density of Aphis fabae where the dose parameter has little influence on the aphicidal activity of the essential oil of Verbena officinalis. On the other hand, the treatment by root absorption acts more on the residual populations and the fecundity of the black bean aphid compared to foliar application, the Biocidal potential of which is accentuated with increasing doses. The formulation has optimized the effectiveness of the essential oil of Verbena officinalis, which resulted in its high toxicity, the most effective root application of which.